Answer:
height = 2m at t = 0s
height = 22.1m at t = 1s
height = 32.4m at t = 2s
height = 32.9m at t = 3s
height = 23.6m at t = 4s
height = 4.5m at t = 5s
Explanation:
Given equation:
H(t) = -4.9t² + 25t + 2 ----------------(i)
The height of the ball is a function of time. Therefore;
(i) At the 0th second. i.e t = 0, we get the height by substituting the value of t = 0 into equation (i). i.e
H(0) = -4.9(0)² + 25(0) + 2
H(0) = 2
∴ At t = 0, the height is 2 meters. This is also obvious in the first statement of the question.
(ii) 1st second. i.e t = 1, we get the height by substituting the value of t = 1 into equation (i). i.e
H(1) = -4.9(1)² + 25(1) + 2
H(1) = 22.1
∴ At t = 1, the height is 22.1 meters.
(iii) 2nd second. i.e t = 2, we get the height by substituting the value of t = 2 into equation (i). i.e
H(2) = -4.9(2)² + 25(2) + 2
H(2) = 32.4
∴ At t = 2, the height is 32.4 meters.
(iv) 3rd second. i.e t = 3, we get the height by substituting the value of t = 3 into equation (i). i.e
H(3) = -4.9(3)² + 25(3) + 2
H(3) = 32.9
∴ At t = 3, the height is 32.9 meters.
(v) 4th second. i.e t = 4, we get the height by substituting the value of t = 4 into equation (i). i.e
H(4) = -4.9(4)² + 25(4) + 2
H(4) = 23.6
∴ At t = 4, the height is 23.6 meters.
(vi) 5th second. i.e t = 5, we get the height by substituting the value of t = 5 into equation (i). i.e
H(5) = -4.9(5)² + 25(5) + 2
H(5) = 4.5
∴ At t = 5, the height is 4.5 meters.